Social media communication spaces to develop literacies in a Higher Education classroom context - Harran, Marcelle; Olamijulo, Christianah (South African Journal of Higher Education, 2016)
This study explores how social media or social networking sites (SNSs) such as Facebook facilitate communication spaces as well as literacies development in a Higher Education (HE) language classroom context. This study’s overarching theoretical orientation is social which challenges many contemporary writing theory and pedagogy assumptions. A social orientation necessitates stepping back from pedagogical issues involved in the teaching and learning of writing and trying to find out how writing is actually used in a range of contexts, including social media. Literacies development, therefore, cannot be separated from the “effects of social context” (Baynham 1995, 52) as writing is a “supremely social act” (Basso 1974:432 in Baynham 1995:42). The qualitative study was situated in a comprehensive university and analyses the perspectives of 17 Public Management first-year English Additional Language participants on the use of the Facebook group page as a communication space in the language class. The data collection included the student Facebook group page postings, focus group interviews and journal reflection reports. Content analysis was used to code the data and access was identified as a critical orientation criterion to identify dominant themes from the data sources. The study found that the participants preferred Facebook as a communication space because of convenience, mobility, learning freedom and team work. However, an access constraint that emerged was limited air time as mobiles were mostly used to access the Facebook site. Although the participants often used informal texting in their wall postings, the research findings revealed that Facebook as a SNS could facilitate teacher-student communication if managed effectively.